Is carbon trading working for construction companies green development ? Evidence from listed Chinese companies - Tian, Jinzhao; Liu, Yisheng; Lan, Mengru (Frontiers in Environmental Science, 2024)
This study investigates the impact of China's carbon emission trading (CET) framework on the green development of the construction sector, a topic that has been underexplored. Utilizing annual data from 107 publicly listed construction companies from 2007 to 2022, we apply green total factor productivity (GTFP) as a metric for green development. Our findings reveal that GTFP increased by 0.36 during this period. Using the Difference-in-Differences (DID) methodology, we account for factors such as market dimensions, ownership structure, financial stability, geographical location, and state financial aid. The interaction term coefficient in our model is 0.0089, significant at the 1% level, indicating that CET implementation has significantly improved GTFP in construction enterprises.Heterogeneity analysis further shows that the CET's impact is more pronounced in large-scale, state-owned, highly indebted enterprises, those located in the eastern region, and those receiving government subsidies, with coefficients of 0.112, 0.0108, 0.0092, 0.0133, and 0.0099, respectively, all significant at the 1% level. These results underscore the importance of unified market development and tailored governance strategies. The study concludes with policy recommendations and calls for further research to explore CET's nuanced impacts across different sectors and regions.